2016
DOI: 10.1210/jc.2016-2163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype and Previous GH Treatment on Adiposity in Adults With Prader-Willi Syndrome

Abstract: A deletion genotype in adults with PWS is associated with increased BMI. GH treatment in childhood and/or adolescence limits this deleterious phenotypic effect with improved adiposity markers. This study suggests relationships between the molecular phenotype of PWS and adipose tissue development as well as sensitivity to GH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
2
46
3
Order By: Relevance
“…In a previous study, it was shown that PWS subjects with deletion had increased BMI and fat mass when compared with subjects with the disomy. 21 In our patient group the differences in gut microbiota composition between patients with deletion and patients with disomy was correlated by difference in serum triglycerides, although the number of patients was low in the disomy group (n=5). This observation needs further examination in an extended group of subjects.…”
Section: Discussionmentioning
confidence: 62%
“…In a previous study, it was shown that PWS subjects with deletion had increased BMI and fat mass when compared with subjects with the disomy. 21 In our patient group the differences in gut microbiota composition between patients with deletion and patients with disomy was correlated by difference in serum triglycerides, although the number of patients was low in the disomy group (n=5). This observation needs further examination in an extended group of subjects.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, our report showed that among deletion patients, peak levels of cortisol in response to ITT were significantly delayed compared to UPD patients. A number of studies have shown physical, intellectual, and behavioral differences among genetic subtypes of PWS, with more specific physical characteristics of PWS (typical face, hypopigmentation) in patients with deletion (Cassidy & Schwartz, ; Lin et al, ), while adults with deletion have a higher BMI, but the same proportion of fat mass (Coupaye et al, ). Concerning endocrine parameters, we have previously reported that secretion of GH was significantly lower in pediatric patients with mUPD than in patients with deletion (Oto et al,).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning endocrine parameters, we have previously reported that secretion of GH was significantly lower in pediatric patients with mUPD than in patients with deletion (Oto et al,). The frequency of hypothyroidism was higher in patients with deletion than in those with mUPD (Coupaye et al, ). With respect to CAI in PWS, Corrias et al () reported that although both patients with deletion and patients with mUPD showed an overall normal mean peak cortisol level, patients with deletion exhibited poorer responses to low‐dose tetracosactrin stimulation test when compared to patients with mUPD.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with our results: the ambiguity in voluntary productions could be the result of a difficulty in coordinating the mobilization of the AUs necessary to express an emotion. In addition, the muscle mass deficit is higher in people with mUPD [50]. These considerations should be taken into account during early psychomotor care.…”
Section: Discussionmentioning
confidence: 99%